2003
DOI: 10.1021/jm030931w
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Synthesizing Enzyme System as Target for Development of Inhibitors and Inhibitor Combinations against Candida albicansSynthesis and Biological Activity of New 2,4-Diaminopyrimidines and 4‘-Substituted 4-Aminodiphenyl Sulfones

Abstract: The paper describes the design, synthesis, and testing of inhibitors of folate-synthesizing enzymes and of whole cell cultures of Candida albicans. The target enzymes used were dihydropteroic acid synthase (SYN) and dihydrofolate reductase (DHFR). Several series of new 2,4-diaminopyrimidines were synthesized and tested as inhibitors of DHFR and compared with their activity against DHFR derived from mycobacteria and Escherichia coli. To test for selectivity, also rat DHFR was used. A series of substituted 4-ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(70 citation statements)
references
References 52 publications
0
69
0
Order By: Relevance
“…Moreover, when the propargyl compounds were assayed with human DHFR, selectivity ratios as high as 156-fold (Table 1) were observed. The IC 50 value of trimethoprim, 7 µM, is included in these enzyme inhibition assays as a reference and compares similarly with the value obtained with other eukaryotic DHFR species ( Candida albicans 30 µM (Otzen et al, 2004), Pneumocystis carinii 12 µM (Rosowsky et al, 2002), Cryptosporidium 14 µM (Pelphrey et al, 2007), Toxoplasma gondii 8 µM (Pelphrey et al, 2007)).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, when the propargyl compounds were assayed with human DHFR, selectivity ratios as high as 156-fold (Table 1) were observed. The IC 50 value of trimethoprim, 7 µM, is included in these enzyme inhibition assays as a reference and compares similarly with the value obtained with other eukaryotic DHFR species ( Candida albicans 30 µM (Otzen et al, 2004), Pneumocystis carinii 12 µM (Rosowsky et al, 2002), Cryptosporidium 14 µM (Pelphrey et al, 2007), Toxoplasma gondii 8 µM (Pelphrey et al, 2007)).…”
Section: Resultsmentioning
confidence: 86%
“…There have been very few studies focusing on DHFR as an antifungal target. While there has been some effort to develop inhibitors of C. albicans DHFR (CaDHFR) (Czaplinski et al, 1995; Kuyper et al, 1996; Otzen et al, 2004) and the crystal structure of CaDHFR (Whitlow et al, 2001; Whitlow et al, 1997) guided the development of a class of molecules (Chan et al, 1995) with some promising activity, up until now there have been no reported efforts to discover inhibitors of C. glabrata DHFR (CgDHFR).…”
Section: Introductionmentioning
confidence: 99%
“…aMIC 80 in vitro has been reported [41], [42].bMIC 80 of FLC in vitro has been reported [43].cMIC 80 in vitro has been reported in our lab [10].…”
Section: Methodsmentioning
confidence: 79%
“…The structure of compound 20 was confirmed from spectroscopic data. The IR showed band at 1737 cm 35) and inhibitors for several 36) cyclic oxygenase-2 (COX-2). Compounds containing C=N may act as a Michael acceptor for nucleophiles containing NH 2 or sulfhydryl SH groups.…”
Section: Resultsmentioning
confidence: 99%